THE INFLUENCE OF E-MARKETING ON CONSUMER DECISION-MAKING IN TRAVEL AGENCY SERVICES AT DIARY TOUR TRAVEL (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstrak: Penelitian ini bertujuan menganalisis pengaruh e-marketing terhadap pengambilan keputusan konsumen pada Diary Tour Travel, di tengah meningkatnya konsumsi konten digital dalam industri pariwisata. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui wawancara mendalam terhadap 10 konsumen berusia 21-40 tahun yang aktif di media sosial serta analisis konten digital selama tiga bulan. Hasil penelitian mengungkap tiga faktor utama yang memengaruhi keputusan pembelian: (1) kredibilitas informasi melalui testimoni video pelanggan (user-generated content), (2) interaksi personal yang responsif melalui pesan langsung, dan (3) daya tarik konten visual destinasi wisata. Namun, intensitas promosi yang berlebihan menimbulkan efek kontraproduktif seperti kebingungan dan penundaan keputusan. Penelitian ini mengintegrasikan model consumer journey dan konsep customer engagement dalam konteks e-marketing pariwisata, serta menyoroti pola perjalanan konsumen yang bersifat non-linear. Kebaruan riset ini terletak pada identifikasi titik jenuh konten promosi di segmen digital muda. Implikasi praktisnya mencakup perlunya strategi konten yang seimbang antara promosi, edukasi, dan storytelling guna meningkatkan efektivitas pemasaran digital secara berkelanjutan.Kata Kunci: e-marketing; keputusan konsumen; consumer journey; konten digital; user-generated content; pariwisata digital; fenomenologi. Abstract: This study aims to analyze the influence of e-marketing on consumer decision-making in the context of Diary Tour Travel, amidst the rising consumption of digital content in the tourism industry. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 10 consumers aged 21–40 who are active on social media, as well as digital content analysis over a three-month period. The findings reveal three main factors influencing purchasing decisions: (1) information credibility through customer video testimonials (user-generated content), (2) responsive personal interaction via direct messages, and (3) the visual appeal of destination content. However, excessive promotional intensity produces counterproductive effects such as consumer confusion and decision delays. This study integrates the consumer journey model and the concept of customer engagement within the context of tourism e-marketing, highlighting the non-linear nature of the consumer journey. The novelty of this research lies in the identification of promotional content saturation points among young digital consumers. Its practical implication emphasizes the need for a balanced content strategy between promotion, education, and storytelling to enhance the long-term effectiveness of digital marketing.Keywords: e-marketing; consumer decisions; consumer journey; digital content; user-generated content; digital tourism; phenomenology.
Keywords: e-marketing; consumer decisions; consumer journey; digital content; user-generated content; digital tourism; phenomenology